(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
The practical experience presented analyzes the perception that Early-Childhood and Primary teachers have about the didactic and practical use of Augmented Reality teaching Social Sciences. The innovative nature of Augmented Reality and its learning potential offer a unique, motivating and transforming learning scenario of the current educational reality. We will identify its possibilities as an innovative resource and key element in the development of a culture of technological learning, focused on the area of Social Sciences and educational values. The statistical-descriptive analysis of the data, done through SPSS v24 reflect the importance of expanding teacher training in this tool and the need to promote innovative methodological proposals that support the current, present and technological reality active in the Infant and Primary classrooms.